O32: TRANSPARENCY IN SURGICAL RANDOMISED CONTROLLED TRIALS: CROSS-SECTIONAL, OBSERVATIONAL STUDY. (27th April 2021) - Helliwell, JA; Shelton, B; Mahmood, H; Blanco-Colino, R; Fitzgerald, JE; Harrison, EM; Bhangu, A; Chapman, SJ
Abstract: Introduction: Randomised controlled trials (RCT) often provide the scientific basis on which commissioning and treatment decisions are made. It is essential that their results and methods are reported transparently. The aim of this study was to explore transparency with respect to trial registration, disclosure of funding sources, conflicts of interest (COI), and data sharing. Method: This was a cross-sectional review of surgical RCTs. Data were extracted from RCTs in ten high-impact journals published in the years 2009, 2012, 2015, and 2018. Outcomes of interest were the incidence of reported trial registration, disclosure of funding sources, disclosure of investigator COI, and presence of a statement of data sharing plans. Result: A total of 475 were eligible for analysis. Trial registration was present in 73 (67%) studies in 2009, 137 (84%) in 2012, 111 (89%) in 2015 and 110 (93%) in 2018. Funding statements were provided in 55%, 65%, 69.4%, and 75.4% of manuscripts, respectively. Conflicts of interest statements were provided in 49.5%, 89.1%, 94.6%, and 98.3% of manuscripts, respectively. Data sharing statements were present in only 15 (3.2%) RCTs. Eleven of these were in studies published most recently in 2018. Conclusion: Trial registration, presence of funding statements, and disclosure of personal conflicts of interest in surgical RCTs have improved rapidly over the last 10 years. In contrast, disclosure of data sharing plans is exceptionally low. This may contribute to research waste and represents an essential target for improvement. Take-home message: Trial registration, presence of funding statements, and disclosure of personal conflicts of interest in surgical RCTs have improved rapidly over the last 10 years. In contrast, disclosure of data sharing plans is exceptionally low. This may contribute to research waste and represents an essential target for improvement.